Design, Synthesis and Biological Evaluation of New 5,5-Diarylhydantoin Derivatives as Selective Cyclooxygenase-2 Inhibitors - Afshin ZARGHI; Farin SATTARY JAVID; Razieh GHODSI; Orkideh G. DADRASS; Bahram DARAEI; Mehdi HEDAYATI (MDPI AG, 2011)
A new group of 5,5-diarylhydantoin derivatives bearing a methylsulfonyl COX-2 pharmacophore at the para position of the C-5 phenyl ring were designed and synthesized as selective COX-2 inhibitors. In vitro COX-1/COX-2 inhibition structure-activity relationships identified 5-[4-(methylsulfonyl)phenyl]-5-phenyl-hydantoin (4) as a highly potent and selective COX-2 inhibitor (COX-2 IC50 = 0.077 μM; selectivity index > 1298). It was more selective than the reference drug celecoxib (COX-2 IC50 = 0.060 μM; selectivity index = 405). A molecular modeling study where 4 was docked in the binding site of COX-2 indicated that the p-MeSO2 COX-2 pharmacophore group on the C-5 phenyl ring is oriented in the vicinity of the COX-2 secondary pocket. The results of this study showed that the type of substituent on the N-3 hydantoin ring substituent is important for COX-2 inhibitory activity.